Digitalisation and application of artificial intelligence in public administration - Lajka, Nedzad; Pavicevic, Djordjije; Martic, Vladan; Crvenica, Dejana; Abramovic, Nikola (Transformations In Business & Economics, 2025)
The digitalisation of public administration represents a critical phase in the modernisation of state institutions, transforming traditional administrative processes into more efficient digital formats. The transition from paper-based documents to electronic databases facilitates faster and more transparent information processing, easier data exchange between institutions, and improves citizens’ access to services. The integration of artificial intelligence (AI) into public administration further enhances these processes by enabling task automation and the intelligent analysis and processing of large volumes of data. AI technologies, such as machine learning and natural language processing, enable pattern recognition, trend prediction, and better decision-making in the provision of public services, as well as the identification of potential risks. The synergy between digitalisation and AI reduces administrative burdens, increases efficiency, and allows for more personalised services to citizens. Additionally, it contributes to greater transparency and accountability in public institutions by facilitating the monitoring of activities and decision-making. This paper explores the extent and scope of digitalisation and AI implementation in the public administration of Montenegro, analysing their impact on the efficiency, accessibility, and quality of services. The aim is to assess how these technologies can enhance public services and citizens’ trust, making institutions faster, more transparent, and better aligned with citizens’ needs.